Distribution of Hotspots and Forest and Land Fire Control Efforts - Rizwan, Achmad; Hendarso, Yoyok; Saptawan, Adriyan; Damiri, Nurhayati (Journal La Lifesci, 2024)
Forest fires are a common ecosystem disturbance globally and have a significant impact on the environment and human life. Ecologically, fires result in decreased land productivity, loss of forest economic value, and threats to biodiversity. The study was conducted quantitatively and qualitatively with secondary and primary data. The data shows fluctuations in the number of hotspots and the area of burned land from 2019 to 2024. Major fires occurred in 2019 and 2023, while a significant decline was seen in 2020 and 2024. This decline reflects the effectiveness of fire mitigation involving the government and the community. Efforts that have been made to reduce the risk of forest and land fires in OKI Regency include peatland rewetting, community education, peatland-based economic empowerment, joint patrols, and the active role of the Fire Aware Community (MAPI) group. The use of satellite-based monitoring technology is also an important step in fire monitoring and mitigation. Preventing forest and land fires in the future requires a comprehensive and sustainable approach, including law enforcement against illegal land burning, increasing patrols, and strengthening community education. Collaboration between stakeholders such as BPBD, local governments, communities, and the private sector is very important to maintain the stability of forest and land fire reduction in the OKI region.